2015
DOI: 10.1515/hsz-2014-0295
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic thiol switches regulating basic cellular functions: GAPDH as an information hub?

Abstract: Cytosolic glyceraldehyde 3-phosphate dehydrogenase (GAPDH, E.C. 1.2.1.12) is present in all organisms and catalyzes the oxidation of triose phosphate during glycolysis. GAPDH is one of the most prominent cellular targets of oxidative modifications when reactive oxygen and nitrogen species are formed during metabolism and under stress conditions. GAPDH harbors a strictly conserved catalytic cysteine, which is susceptible to a variety of thiol modifications, including S-sulfenylation, S-glutathionylation, S-nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
134
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(136 citation statements)
references
References 102 publications
2
134
0
Order By: Relevance
“…Precedents exist for distinct biochemical activities (for a given protein) that are dependent on specific redox modifications. The catalytic cysteine of cytosolic glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is susceptible to a variety of reversible thiol modifications, including sulfenylation, glutathionylation, nitrosylation, and sulfhydration (37)(38)(39)(40)(41); as a consequence of distinct modification inputs, GAPDH transduces alternative signals for adaptive adjustment of metabolism or cell death (42). Yet, for BiP, we observe similar activity changes for glutathionylated and sulfenylated BiP.…”
Section: Discussionmentioning
confidence: 80%
“…Precedents exist for distinct biochemical activities (for a given protein) that are dependent on specific redox modifications. The catalytic cysteine of cytosolic glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is susceptible to a variety of reversible thiol modifications, including sulfenylation, glutathionylation, nitrosylation, and sulfhydration (37)(38)(39)(40)(41); as a consequence of distinct modification inputs, GAPDH transduces alternative signals for adaptive adjustment of metabolism or cell death (42). Yet, for BiP, we observe similar activity changes for glutathionylated and sulfenylated BiP.…”
Section: Discussionmentioning
confidence: 80%
“…While our isotopic tracing data clearly indicate that GSTP1 inhibition leads to an impairment in the ATP-generating steps of glycolysis downstream of GAPDH, we do not yet understand the mechanism through which this occurs. GAPDH activity is dependent on a highly reactive catalytic cysteine that coordinates the interconversion between 1,3-bisphosphoglycerate into glyceraldehyde-3-phosphate and is particularly sensitive to oxidation by agents such as hydrogen peroxide or other oxidants which can inhibit GAPDH activity (Hildebrandt et al, 2015). Reports have also shown that GAPDH can even be inhibited by its reactive 1,3-bisphosphoglycerate product on a hyper-reactive and functional lysine to inhibit its activity (Moellering and Cravatt, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear function of GAPDH in plant systems is not clear, but it probably acts as a coactivator of NADP-MDH expression by binding to the NADP-malate dehydrogenase (NADP-MDH) gene and, consequently, increases the capacity of the malate valve to balance the cellular energy supply (Scheibe 2004, Becker et al 2006, Hildebrandt et al 2015.…”
Section: Discussionmentioning
confidence: 99%